The impact of cultural authenticity on brand uniqueness and willingness to try: The case of Chinese brands and US consumers. Issue 4 (12th September 2016) - Southworth, Sarah Song; Ha-Brookshire, Jung
Abstract : Purpose: In response to today's marketplace in which many Asian brands are trying to expand their businesses into Western nations, this study investigated the strategic use of cultural authenticity that Asian brands may employ for their success. Although the benefits of using cultural heritage in brand strategies have been noted by past literature, the efficacies of how Asian brands can use brand logo designs to positively influence their brand success have not been studied. To fill this gap, the purpose of this paper is to examine how Chinese brands can increase willingness to try among US consumers by establishing brand uniqueness via culturally authentic brand logo designs. Design/methodology/approach: The data from 289 respondents via online between-subjects factorial experimental research surveys were collected using a national US population as the sample frame. The Chinese brand logos communicating Asian heritage were created by manipulating the cultural authenticity of the brand logo mark and the language of the logotype. Findings: The results suggested that the Asian-themed brand logo is an important tool in exuding a Chinese brand's sense of cultural authenticity to US consumers. In turn, the perception of cultural authenticity for the Chinese brand positively influenced the US consumers' perceptions of the brand's uniqueness, which led to greater willingness to try the brand. Originality/value: The research provides empirical insights into how "Asian-ness" can be manifested via brand logos to convey cultural authenticity as well as to build perceived brand uniqueness and the willingness to try among US consumers.